(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This article analyzes the process of rational choice formation and capital mobilization among women working as culinary vendors in the Piwang Beach area, Natuna Regency, one of Indonesia’s outermost islands. The study employed a qualitative approach with an interpretive paradigm. Data were collected through in-depth interviews, observation, and documentation with six informants purposively selected based on their involvement in informal culinary businesses. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, then interpreted using Coleman’s Rational Choice theory and Bourdieu’s concepts of economic, social, and cultural capital. The results present descriptive findings on informant profiles, values, preferences, and forms of capital found in the field. The Discussion section interprets these findings through a more in-depth theoretical framework. The findings indicate that rational choice is formed through the construction of business accessibility values ​​and layered preferences (economic, social, and cultural). The three forms of capital—economic, social, and cultural—are mobilized synergistically with varying intensities across informants. This article proposes an analytical model of ’structured agency’ to explain the paradox between structural coercion and the active choices of women informal workers in the archipelago.